Targeted Delivery of siRNA‐Generating DNA Nanocassettes Using Multifunctional Nanoparticles. Issue 11 (6th January 2013) - Cho, Young‐Seok; Lee, Gee Young; Sajja, Hari Krishna; Qian, Weiping; Cao, Zehong; He, Weiling; Karna, Prasanthi; Chen, Xiaoyuan; Mao, Hui; Wang, Y. Andrew; Yang, Lily
Abstract Molecular therapy using a small interfering RNA (siRNA) has shown promise in the development of novel therapeutics. Various formulations have been used for in vivo delivery of siRNAs. However, the stability of short double‐stranded RNA molecules in the blood and efficiency of siRNA delivery into target organs or tissues following systemic administration have been the major issues that limit applications of siRNA in human patients. In this study, multifunctional siRNA delivery nanoparticles are developed that combine imaging capability of nanoparticles with urokinase plasminogen activator receptor‐targeted delivery of siRNA expressing DNA nanocassettes. This theranostic nanoparticle platform consists of a nanoparticle conjugated with targeting ligands and double‐stranded DNA nanocassettes containing a U6 promoter and a shRNA gene for in vivo siRNA expression. Targeted delivery and gene silencing efficiency of firefly luciferase siRNA nanogenerators are demonstrated in tumor cells and in animal tumor models. Delivery of survivin siRNA expressing nanocassettes into tumor cells induces apoptotic cell death and sensitizes cells to chemotherapy drugs. The ability of expression of siRNAs from multiple nanocassettes conjugated to a single nanoparticle following receptor‐mediated internalization should enhance the therapeutic effect of the siRNA‐mediated cancer therapy.